2020
DOI: 10.1136/bjophthalmol-2019-315726
|View full text |Cite
|
Sign up to set email alerts
|

Real-world management of treatment-naïve diabetic macular oedema: 2-year visual outcome focusing on the starting year of intervention from STREAT-DMO study

Abstract: Background/aimsTo investigate the yearly change of real-world outcomes for best corrected visual acuity (BCVA) after 2-year clinical intervention for treatment-naïve diabetic macular oedema (DMO).MethodsRetrospective analysis of aggregated, longitudinal medical records obtained from 27 retina specialised institutions in Japan from Survey of Treatment for DMO database. A total of 2049 treatment-naïve centre involving DMO eyes of which the initial intervention started between 2010 and 2015, and had been followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Recovery and retention of useful visual acuity (decimal BCVA ≥0.5) is a primary treatment goal for macular disease. 26 In the present study, BCVA was improved or maintained at 24 months from baseline in 89.7% of patients, whereas only 37.5% had a decimal BCVA >0.5 at the final visit. This suggests that the rate of achieving the treatment goal in current clinical practice might be insufficient and that there is a need for early intervention and an improved regimen (eg, a treat-and-extend regimen) in order to obtain better vision and achieve better patient satisfaction.…”
Section: Discussionsupporting
confidence: 42%
“…Recovery and retention of useful visual acuity (decimal BCVA ≥0.5) is a primary treatment goal for macular disease. 26 In the present study, BCVA was improved or maintained at 24 months from baseline in 89.7% of patients, whereas only 37.5% had a decimal BCVA >0.5 at the final visit. This suggests that the rate of achieving the treatment goal in current clinical practice might be insufficient and that there is a need for early intervention and an improved regimen (eg, a treat-and-extend regimen) in order to obtain better vision and achieve better patient satisfaction.…”
Section: Discussionsupporting
confidence: 42%
“…In this study, the prompt group received 5.11 ± 2.59 injections per year with change in BCVA of −0.14 ± 0.29, and the deferred group received 3.01 ± 1.55 injections with BCVA change of −0.04 ± 0.36. In the Mercury study, a recent multicenter report of PRN regimen with ranibizumab in Japan, the change in BCVA were −0.10 ± 0.24 in the eyes that underwent five or more injections and 0.03 ± 0.31 in the eyes that received 3-4 injections per year [18]. With regard to the number of injections and the change in visual acuity, the results of both studies showed comparable outcomes.…”
Section: Discussionmentioning
confidence: 93%
“…This was a secondary analysis of a large‐scale multicenter retrospective study of Survey of Treatment for DME (STREAT‐DME) study conducted by the Japan Clinical Retina Study (J‐CREST) group 16 , 19 . The STREAT‐DME study conformed to the tenets of the Declaration of Helsinki, and institutional review board approval was granted at each institution.…”
Section: Methodsmentioning
confidence: 99%